DEVELOPING THEMATIC LEARNING MODULE BASED ON ETHNOSCIENCE ORIENTED OUTDOOR LEARNING STRATEGY TO IMPROVE STUDENT’S LEARNING OUTCOMES IN PRIMARY SCHOOL - Siswoyo, Andika Adinanda (UIN Sunan Kalijaga Yogyakarta, 2021)
The difficulty of students to understand science concepts in thematic learning requires innovation of the appropriate teaching materials. Meanwhile, the existence of salt ponds around students can be used as oriented outdoor learning. Therefore, this study aims to develop ethnoscience-based thematic modules implemented through outdoor learning strategies. The subjects were 40 grade VI students at Public Elementary School (or called SDN) Padelegan Pamekasan with different academic abilities and gender. The test results of learning data validity and effectiveness of modules were obtained through observation sheet instruments and questionnaires. According to the results, (1) validity modules were in the valid category, based on assessment of material and learning design experts, (2) the module’s effectiveness is in the effective category. Therefore, it can be concluded that the module strategy is worth using and improving science understanding for thematic learning in elementary schools.